Mycobacterium tuberculosis surface protein Rv0227c contains high activity binding peptides which inhibit cell invasion (2012)
Mycobacterium tuberculosis surface proteins involved in target cell invasion may be identified as a strategy for developing subunit-based, chemically-synthesized vaccines. The Rv0227c protein was thus selected to assess its role in the invasion and infection of Mycobacterium tuberculosis target cells. Results revealed Rv0227c localization on mycobacterial surface by immunoelectron microscopy and Western blot. Receptor-ligand assays using 20-mer, non-overlapping peptides covering the complete Rv0227c protein sequence revealed three high activity binding peptides for U937 phagocytic cells and seven for A549 cells. Peptide 16944 significantly inhibited mycobacterial entry to both cell lines while 16943 and 16949 only managed to inhibit entrance to U937 cells and 16951 to A549 cells. The Jnet bioinformatics tool predicted secondary structure elements for the complete protein, agreeing with elements determined for such chemically-synthesized peptides. It was thus concluded that high activity binding peptides which were able to inhibit mycobacterial entry to target cells are of great importance when selecting peptide candidates for inclusion in an anti-tuberculosis vaccine. © 2012 Elsevier Inc.